Climate Adaptation as Organizational Learning: A Grounded Theory Study on Manufacturing Companies in a Bavarian Region - Sophie Fischer; Luzia Keupp; Heiko Paeth; Michael Göhlich; Jan Schmitt (MDPI AG, 2022)
Climate adaptation supports organizations in dealing with the current and projected effects of climate change by recognizing challenges as opportunities and increasing their economic efficiency. Based on the regional climate model REMO and 13 expert interviews with representatives from mainly manufacturing companies analyzed by the Grounded Theory methodology, this contribution aims to outline actual and future challenges of climate adaptation in the investigated region. We analyze how manufacturing companies respond to climate change and assess the main promoters and barriers of organizational learning in the context of climate adaptation. The expert interviews confirm the importance for companies of having a concrete business case for any strategies and of increasingly making their processes and manufacturing more transparent, through supply chain assessments. In accordance, a focus on strategic management levels is crucial for organizational learning processes as they are responsible for development, mobilization of resources and realization of adaptation concepts.